2019
DOI: 10.1063/1.5109713
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature exchange bias in antiferromagnetic composite BiFeO3-TbMnO3

Abstract: We report the presence of giant spontaneous exchange bias (H SEB ) in a hard and soft antiferromagnetic composite of BiFeO 3 -TbMnO 3 (BFO-TMO in 7:3 and 8:2 ratio). The H SEB varies between 5-778Oe, but persists up to room temperature with a maximum near a spin reorientation transition temperature observed from magnetization vs. temperature measurement in Zero-field cooled (ZFC) and Field cooled (FC) modes. Isothermal remnant magnetization measurements at room temperature indicate the presence of an interfaci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…From the curve, an evident bifurcation below 50 K can be observed; furthermore, the M ZFC and M FC curves do not merge in the temperature range from 5 K to 300 K. A plot of ∆M (=M FC −M ZFC ) vs T(K), as shown in the inset of figure 2(a), indicates that the blocking temperature may be above 380 K. It is found that M vs T for a higher magnetic field (5 kOe) has dominant bifurcation below 20 K, but ∆M (=M FC −M ZFC ) vs T does not merge in the measured temperature range. The bifurcation persists for applied fields, even above the anisotropy field, suggesting the role of the magnetic interface layer in the observed temperature-dependent magnetisation [28].…”
Section: Resultsmentioning
confidence: 83%
“…From the curve, an evident bifurcation below 50 K can be observed; furthermore, the M ZFC and M FC curves do not merge in the temperature range from 5 K to 300 K. A plot of ∆M (=M FC −M ZFC ) vs T(K), as shown in the inset of figure 2(a), indicates that the blocking temperature may be above 380 K. It is found that M vs T for a higher magnetic field (5 kOe) has dominant bifurcation below 20 K, but ∆M (=M FC −M ZFC ) vs T does not merge in the measured temperature range. The bifurcation persists for applied fields, even above the anisotropy field, suggesting the role of the magnetic interface layer in the observed temperature-dependent magnetisation [28].…”
Section: Resultsmentioning
confidence: 83%
“…The Mn 2 p 3/2 peaks are at BE 640.61 and 642.08 eV and Mn2 p 1/2 peaks are at BE 652.31 and 653.78 eV for the present system, whereas one satellite peak is also present at 645.91 eV for the BTFMO91 system. [ 14,74,75 ] Thus, there exists a mixed oxidation state of Mn (Mn 3+ and Mn 4+ ) in our system.…”
Section: Resultsmentioning
confidence: 93%
“…[10] Different approaches have been attempted to reduce leakage currents such as synthesis using various chemical routes, doping at the A and B-site of BFO, and growing high-quality single crystal and thin films. [11][12][13][14][15] We choose the ionic-substitution strategy over the others as it can suppress the spiral spin structure and enhance its magnetization. Chemical substitution at the Bi/Fe sites of BFO with appropriate ionic radius elements has been reported to produce a stable perovskite phase.…”
mentioning
confidence: 99%
“…However, for EPCMO, step size (∆M) is much smaller, thus, the possibility of field-induced spin flop behind the origin of MMT can be ruled out. Additionally, a close view of the M(H) curve shows that the loop is asymmetric around the origin, indicative of the presence of spontaneous EB [39,51], as M(H) loop was recorded in ZFC mode, in EPCMO at low temperature. The magnitude of EB field is given as, H EB = (H C1 + H C2 )/2 [51], where H C1 and H C2 are the magnitudes of magnetic fields at which magnetization becomes zero, which is found to be around 1.17 kOe for EPCMO.…”
Section: Magnetic Studymentioning
confidence: 79%